Is it early enough? The authentic meaning of the pediatric palliative approach between early and late referral in pediatric oncology: a case study - Santini, Anna; Avagnina, Irene; Affinita, Maria C.; Zanin, Anna; Benini, Franca (Frontiers in Oncology, 2024)
The literature widely supports the benefits of early integration of palliative care into pediatric oncological care; however, many barriers to its successful integration remain. Integrating palliative care as early as possible in the oncology pathway is critical, but other criteria are relevant to positive results. This paper aims to contribute to the early/late referral dualism in pediatric palliative care (PPC) and highlight the importance of a collaborative approach between oncologists and palliative care teams. This study investigates the impact of early versus late referral to PPC, intersecting it with the synergy work between services and the related outcomes. The four pediatric cancer cases were selected based on clinical (e.g., disease duration, multiple treatments, and pain management), management (e.g., involvement of multiple services and multiple home–hospital transitions), and relevance of multidisciplinary team (e.g., difficult clinical decisions and ethical discussions) criteria. A mixed-methods approach was employed, combining qualitative case analysis using clinical diaries, literature review, and practice guidelines development. Critical clinical information, time course, clinician–family communication, and patient involvement were analyzed. The outcomes show how simultaneous care creates continuous discussion and dialogue between professionals. The results indicate the importance of better communication and care coordination to improve patient and family satisfaction, highlighting the uniqueness of the pediatric field and the relationship with children and families. Through the discussion of clinical cases and a literature review, we provide practical guidance for clinicians working in oncology and PPC. These findings underscore the crucial need for a multidisciplinary approach in pediatric oncology, advocating policy changes to support early PPC integration and translate it into complementarity best operating practices. In conclusion, besides assessing the timeliness of referral to the PPC service, the synergy, harmony, and choral work of the professionals involved are equally valuable for a quality-of-life-oriented care plan.